2001
DOI: 10.1902/jop.2000.72.9.1246
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors and Their Relation to Metabolic Control and Periodontal Status in Type 2 Diabetic Patients: A Model Tested Using a Linear Structural Relations Program

Abstract: The severity of the 2 diseases seemed to be connected indirectly through health behaviors such as diet behavior and oral health behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
21
0
2
Order By: Relevance
“…The evidence of common behavioral etiology has recently been shown in dentistry, where it has been found that general health behavior is linked to dental health behavior to at least some degree (Payne and Locker, 1996;Sakki et al, 1998;Kawamura et al, 2001) and, consequently, to dental health status (Sakki et al, 1994(Sakki et al, , 1995. This supports the assumption that dental and general health behaviors might have some determinants in common.…”
Section: Introductionmentioning
confidence: 53%
“…The evidence of common behavioral etiology has recently been shown in dentistry, where it has been found that general health behavior is linked to dental health behavior to at least some degree (Payne and Locker, 1996;Sakki et al, 1998;Kawamura et al, 2001) and, consequently, to dental health status (Sakki et al, 1994(Sakki et al, , 1995. This supports the assumption that dental and general health behaviors might have some determinants in common.…”
Section: Introductionmentioning
confidence: 53%
“…While SEM was developed for use in the behavioral and social sciences, some researchers have used this method in the dental field (18,19). Data on a behavior science application of SEM in a clinical setting has only been published in one previous report, which proposed structural relationships between dental anxiety and mood in the adult population (20).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, poor metabolic control has been found to relate to more AL (Seppälä et al 1993, Bridges et al 1996), bone loss (Seppälä et al 1993, Taylor et al 1998) and advanced periodontal disease (Collin et al 1998). However, many studies have failed to reveal any conclusive association between metabolic control and the severity of periodontitis (Barnett et al 1984, Rylander et al 1986, Bačić et al 1988, Hayden & Buckley 1989, Sastrowijoto et al 1989, De Pommereau et al 1992, Pinson et al 1995, Thorstensson et al 1996, Kawamura et al 2001). At the background of these contradictory results, there may be variation in the classification of metabolic control or a failure to control the confounding factors.…”
mentioning
confidence: 99%